IMPLEMENTASI NILAI-NILAI KRISTIANI DALAM LAYANAN BIMBINGAN DAN KONSELING UNTUK PENGUATAN KARAKTER SISWA - Wirandini Bulawan; Nestin Palimbong; Milka Datu Limbong; Elviana Fransina; Natalia (ADISAM PUBLISHER, 2026)
This study aims to examine the implementation of Christian values ​​within guidance and counseling services as a means of strengthening student character. Character strengthening is a crucial aspect of education, as it plays a role in shaping students who are not only academically excellent but also possess sound moral and spiritual integrity. The study employs a library research method with a descriptive qualitative approach. Data were gathered through a review of various books, journal articles, and scholarly sources relevant to Christian values, guidance and counseling, and character education. The findings indicate that Christian values such as love, honesty, responsibility, humility, forgiveness, and social concern can be integrated into the delivery of guidance and counseling services through various forms of student support. Implementing these values ​​positively impacts student character development by enhancing integrity, discipline, empathy, self-control, and spiritual awareness. Thus, guidance and counseling services grounded in Christian values ​​can serve as an effective tool for supporting holistic and sustainable character strengthening among students.